Beyond Compliance: How Quality Management Transforms Accountability in Indonesian Higher Education - Kasimbara, Rachma Putri; Setiawan, Deny; Purnomo, Eko Nurhaji (Universitas Muhammadiyah Magelang, 2026)
Accountability has become a critical issue in higher education management, particularly in relation to quality assurance and performance transparency. This study aims to examine how educational quality management strengthens institutional accountability through internal quality assurance practices in Indonesian higher education. The study employs a qualitative semi-empirical approach by integrating a systematic literature review with document analysis and reflective evaluation of Internal Quality Assurance Systems implemented through the PDCA cycle (Establishment, Implementation, Evaluation, Control, and Improvement). The analysis focuses on how quality management processes are translated into accountability mechanisms through evaluation-based decision-making and continuous improvement. The findings indicate that educational quality management contributes to accountability when internal quality assurance is implemented as an integrated and evaluative process rather than a compliance-oriented administrative activity. Leadership commitment, systematic use of evaluation results, and the development of a quality-oriented organizational culture are identified as key factors influencing the effectiveness of accountability mechanisms. The study concludes that accountability in higher education is not merely an external reporting obligation but an outcome of educational quality management embedded within internal quality assurance systems. These findings provide practical implications for higher education leaders and quality assurance units in strengthening accountable governance and sustainable quality improvement.